POMIĘDZY DECENTRALIZACJĄ A OMNIPOTENCJĄ. STOSUNKI SAMORZĄDU TERYTORIALNEGO I ADMINISTRACJI RZĄDOWEJ W II I III RZECZYPOSPOLITEJ - Bojarowicz, Tomasz (Polityka i Społeczeństwo, 2021)
The aim of the study is to compare the institutional solutions and practical activities of the government and local government administration in two periods: the Second and the Third Republic of Poland. Because of the need to refer to the documents from the period of the Second Republic of Poland, it was necessary to refer to the historical method. The study is based on the comparison of two orders from different periods, therefore it was necessary to use the comparative method for the purpose of the analysis conducted. In the study also a system approach was applied to the analysis of institutional solutions. Decentralist and centralist concepts clashed both in the period of the Second Republic of Poland and during the political transformation. The beginnings of the political change were characterised by the predominance of naturalist tendencies, while in the further stages of the development of the Polish state there were growing tendencies to increase the omnipotence of the state.